Free Will, Responsibility, and Crime : An Introduction. - Levy, Ken M. ([Place of publication not identified] : Routledge, 2019)
In his book, philosopher and law professor Ken Levy explains why he agrees with most people, but not with most other philosophers, about free will and responsibility. Most people believe that we have both - that is, that our choices, decisions, and actions are neither determined nor undetermined but rather fully self-determined. By contrast, most philosophers understand just how difficult it is to defend this "metaphysical libertarian" position. So they tend to opt for two other theories: "responsibility skepticism" (which denies the very possibility of free will and responsibility) and "compatibilism" (which reduces free will and responsibility to properties that are compatible with determinism). In opposition to both of these theories, Levy explains how free will and responsibility are indeed metaphysically possible. But he also cautions against the dogma that metaphysical libertarianism is actually true, a widespread belief that continues to cause serious social, political, and legal harms. Levy's book presents a crisp, tight, historically informed discussion, with fresh clarity, insight, and originality. It will become one of the definitive resources for students, academics, and general readers in this critical intersection among metaphysics, ethics, and criminal law. Key features: Presents a unique, qualified defense of "metaphysical libertarianism," the idea that our choices, decisions, and actions can be fully self-determined. Written clearly, accessibly, and with minimal jargon - rare for a book on the very difficult issues of free will and responsibility. Seamlessly connects philosophical, legal, psychological, and political issues. Will be provocative and insightful for professional philosophers, students, and non-philosophers.
Ch. 1. Incompatibilism Versus Compatibilism Introduction Incompatibilism Indeterminism Compatibilists' First Objection to Incompatibilism Metaphysical Libertarianism Three Possible Locations for Indeterminism Metaphysical Libertarianism's Underlying Theory of the Self as Pure Substance Compatibilists' Renewed Randomness Objection Two Problems with Metaphysical Libertarianism Compatibilism and the Harmony Condition Frankfurt's Identification Theory Incompatibilists: Identification Is Insufficient for Free Will Traditional Compatibilism and the Ability to Do Otherwise Rationality Compatibilism Compatibilists Versus Metaphysical Libertarians Compatibilists Versus Free Will Skeptics Conclusion Ch. 2. New Compatibilism Versus the Ought-Implies-Can Principle Introduction Five Definitions of Free Will Moral Responsibility Frankfurt's Argument Against the Principle of Alternative Possibilities The Maxim Argument The Anti-Maxim Position Objections and Replies Why Frankfurt's Conclusion Defeats the Maxim Conclusion Ch. 3. Moral Responsibility Does Not Require the Power to Do Otherwise, But It Does Require at Least One Alternative Possibility Introduction Three Objections to Frankfurt's Argument Against PAP David Hunt's Blockage Argument Hunt's Neural Wall Why Hunt's Blockage Argument Fails: The Dilemma Argument Against Blockage Implications for Incompatibilism Conclusion Ch. 4. The Puzzle of Responsibility Introduction The Responsibility Axiom and Two Kinds of Blameless Wrongdoing The Blameless Wrongdoer Argument A Working Conception of Responsibility The Sympathy Argument Just Criminal Punishment Does Not Necessarily Require Moral Responsibility Conclusion Ch. 5. Contrary to Responsibility Skepticism, Metaphysical Libertarianism Is Metaphysically Possible Introduction Responsibility Skepticism The Responsibility Skeptic's Objection to Robert Kane's Defense of Metaphysical Libertarianism Supplementing Kane's Metaphysical Libertarianism with Susan Wolf's Rationalist Theory of Responsibility The Randomness Objection One Last Defense of Metaphysical Libertarianism Over Responsibility Skepticism Agent Causation Conclusion Ch. 6. The Dark Side of Metaphysical Libertarianism Introduction The Self-Made-Man Postulate Success Is (Almost?) Entirely a Matter of Good Luck Constitutive Luck and Responsibility Skepticism Situational Luck Failure Is (Almost?) Entirely a Matter of Bad Luck Conclusion Ch. 7. Criminal Responsibility Does Not Require Moral Responsibility: Psychopaths Introduction Psychopathy Defined A. A Working Definition of Psychopathy B. Psychological Community's Definition C. Possible Problems with the PCL-R D. Differences between Psychopathy and Antisocial Personality Disorder Three Consequentialist Reasons for Criminally Punishing Psychopaths Three Arguments that Psychopaths Are Not Morally Responsible for Their Criminal Behavior A. First Argument that Psychopaths Are Not Morally Responsible for Their Criminal Behavior: Normative Incompetence B. Second Argument that Psychopaths Are Not Morally Responsible for Their Criminal Behavior: Inability To Do Otherwise C. Third Argument that Psychopaths Are Not Morally Responsible for Their Criminal Behavior: No Self-Control The Insanity Defense A. Assumptions Underlying the Insanity Defense B. Different Versions of the Insanity Defense Four Arguments that Psychopaths Are Insane A. First Argument that Psychopaths Are Insane B. Second Argument that Psychopaths Are Insane C. Third Argument that Psychopaths Are Insane D. Fourth Argument that Psychopaths Are Insane Why the Criminal Justice System Regards Psychopaths as Criminally Responsible Why Psychopaths Are Criminally Responsible Even Though They Are Not Morally Responsible A. Why Criminal Responsibility Does Not Require Moral Responsibility B. Why Moral or Emotional Understanding of the Law Is Not Necessary for Criminal Responsibility C. Psychopaths Have Sufficient Control over Their Behavior Conclusion Ch. 8. Criminal Responsibility Does Not Require Moral Responsibility: Situationism Introduction The Excuses A. Stephen Morse's Dualist Theory of the Excuses B. A Monist Theory of the Excuses Situationism and Moral Responsibility A. Our Nearly Universal Capacity for Cruelty B. The Dispositionism Paradox C. Situationism and Norm-Compliance D. Stanley Milgram's Shock Experiment E. Arguments for Recognizing Situationism as a Moral Excuse Situationism and Criminal Responsibility The Insanity Defense: Two Final Objections Conclusion Ch. 9. Addiction, Indoctrination, and Responsibility Introduction Addiction The "Addiction Negates Responsibility" Argument Addiction Versus Weakness of Will The Disease theory Is Actually Consistent with Responsibility for Addiction Indoctrination Doxastic Control Greedy, Addict, Mr. Insane, and the Dangers of Responsibility Skepticism Conclusion
OCLC-licensed vendor bibliographic record.
Keywords: Free will and determinism; Criminal behavior, Prediction of; PHILOSOPHY / General